How might climate changes and preference changes affect the competitiveness of the world's wine regions? - Kym Anderson (Wine Economics and Policy, 2017)
Winegrape production is generally considered riskier in cool-climate regions than in warmer ones, yet more producers are looking to invest in such regions. A commonly stated reason is to hedge against global warming, but is there more to it than that? This note reflects on some other supply-side drivers as well as some drivers from the demand side of global wine markets. It first defines what characterizes a cool-climate region; and it ends by drawing implications for the economic future of such cool regions as compared with the world's warmer wine regions.
Keywords: 330; Climate change; Competitiveness; Cool-climate wine